2014
DOI: 10.1097/01.sa.0000443984.97821.e6
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Identification of Gastroesophageal Reflux Disease as a New Risk Factor for Surgical Site Infection in Cerebral Palsy Patients After Spine Surgery

Abstract: Comment by Christopher Stemland, MD Disclosure: The author declares no conflict of interest. REFERENCES 1. Hawn MT, Richman JS, Vick CC, et al. Timing of surgical antibiotic prophylaxis and the risk of surgical site infection. JAMA Surg. 2013;148(7): 649Y657.2. Canani RB, Cirillo P, Roggero P, et al. Therapy with gastric acid inhibitors increases the risk of acute gastroenteritis and community-acquired pneumonia in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Lastly, of all the preoperative variables analyzed in our study, GERD was identified as an independent predictor of organ/space SSI. A recent study of SSI following spine surgery suggests that patients with GERD may be at increased risk for SSI secondary to suboptimal nutritional status [27]. Gastric acid inhibitors also decrease the acid barrier and alter leukocyte function, both of which may influence inherent systemic ability to fight infectious organisms.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lastly, of all the preoperative variables analyzed in our study, GERD was identified as an independent predictor of organ/space SSI. A recent study of SSI following spine surgery suggests that patients with GERD may be at increased risk for SSI secondary to suboptimal nutritional status [27]. Gastric acid inhibitors also decrease the acid barrier and alter leukocyte function, both of which may influence inherent systemic ability to fight infectious organisms.…”
Section: Discussionmentioning
confidence: 98%
“…When the multivariable model adjusted for age, ECOG performance status, ASA level, FIGO stage, ascites, RD, and histology was applied to the 689 women who received chemotherapy, superficial SSI remained an independent predictor of worse OS (adjusted HR 1.70, 95% CI 1.06, 2.73) and there was a trend toward worse OS associated with organ/ space SSI (adjusted HR 1.39, 95% CI 0.95, 2.04). The median number of days from surgery to adjuvant chemotherapy (TTC) was significantly less in those without SSI prior to starting chemotherapy compared to the women who had a SSI prior to starting chemotherapy (median (IQR) 31 (27,41) vs. 44 (36, 52) days, P b 0.001). The following factors were identified in a multivariable analysis as being significantly (P b 0.05) associated with TTC: age, ascites, surgical complexity and estimated blood loss.…”
Section: Effect Of Ssi On Survival and Time To Chemotherapymentioning
confidence: 94%